Impaired fibrinolysis is associated with the severity of aortic stenosis in humans. Issue 4 (11th April 2013) - Natorska, J.; Wypasek, E.; Grudzień, G.; Sadowski, J.; Undas, A.
Summary Background A role of fibrinolysis in the pathogenesis of aortic valve stenosis (AS) is unknown, although fibrinolytic proteins have been detected in aortic stenotic valves. Objective To investigate whether impaired fibrinolysis could be associated with AS. Methods and Results We studied 74 patients with AS (43 male, 31 female, aged 62.7 ± 10.7 years) without documented atherosclerotic valvular disease scheduled for isolated valve replacement and 68 controls. The plasma fibrin clot lysis time (CLT) in the presence of tissue factor (TF) and tissue plasminogen activator (tPA), along with plasma plasminogen activator inhibitor‐1 (PAI‐1) were determined. Valvular expression of fibrin and PAI‐1 together with macrophages and mast cells (MC) was evaluated by immunostaining. Patients with AS compared with controls were characterized by a prolonged CLT (median, 110 [54–153] vs. 92.5 [58–115] min, P = 0.0007) and increased plasma PAI‐1 (78.6 [35.5–149] vs. 38.5 [18–61] ng mL−1, P < 0.0001). CLT was correlated with maximal (r = 0.43, P = 0.0002) and mean (r = 0.38, P = 0.001) transvalvular pressure gradients, and aortic valve area (r = −0.59, P < 0.0001). In AS patients, the CLT was positively correlated with the valve leaflet thickness (r = 0.67, P = 0.003), the degree of valve calcification (r = 0.65, P < 0.00001), valvular fibrin (r = 0.54, P = 0.007) and PAI‐1 expression (r = 0.48, P = 0.007). Double‐immunostaining revealed colocalization of valvular PAI‐1 with MC (87 ± 17% cells) and macrophages (48 ± 11% cells) within stenotic valves. Conclusions Hypofibrinolysis might be a marker of severe AS and be implicated in AS progression.